2013
DOI: 10.1097/icl.0b013e3182993921
|View full text |Cite
|
Sign up to set email alerts
|

Application of Senofilcon A Contact Lenses for Therapeutic Bandage Lens Indications

Abstract: Senofilcon A contact lenses are successful in the majority of cases when used for providing protection of corneal exposure and recurrent damage, pain management, barrier protection, and postsurgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…BCLs are widely used after corneal refractive surgery, including laser-assisted subepithelial keratomileusis (LASEK) or photorefractive keratectomy, because they protect the corneal wound, prompt the corneal epithelium to heal, and relieve patients' discomfort [79]. They are also frequently applied to keep the flap in its proper position after LASIK and thus prevent corneal flap–related complications, such as buttonhole flaps, partial flaps, free caps, epithelial defects, and postoperative traumatic dislocation of LASIK flaps [10, 12, 13]. In the present study, we evaluated the effect of BCL application after FS-LASIK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCLs are widely used after corneal refractive surgery, including laser-assisted subepithelial keratomileusis (LASEK) or photorefractive keratectomy, because they protect the corneal wound, prompt the corneal epithelium to heal, and relieve patients' discomfort [79]. They are also frequently applied to keep the flap in its proper position after LASIK and thus prevent corneal flap–related complications, such as buttonhole flaps, partial flaps, free caps, epithelial defects, and postoperative traumatic dislocation of LASIK flaps [10, 12, 13]. In the present study, we evaluated the effect of BCL application after FS-LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the therapeutic effects of BCLs after corneal refractive surgery in alleviating discomfort, facilitating healing by re-epithelialization, promoting visual recovery, and decreasing the risk of postoperative infection [79]. BCLs are also used to keep the flap in its proper position after LASIK [10].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Thus, silicone hydrogels would be better candidates than conventional hydrogel lenses for drug delivery, and SA is already approved for therapeutic use. 35 As yeast cells are able to grow inside the agar, the agar eye models were homogenized and replated on PDA plates. Surprisingly, although the eye models appeared clear for the NA-SA and NA-LB conditions, the plates yielded CFU counts similar to other experimental conditions and the control.…”
Section: Discussionmentioning
confidence: 99%
“…91 The use of BCLs after other refractive surgical procedures has been reported (LASIK, LASEK, epi-LASIK), with many of the patients wearing the lenses successfully for 4 to 6 days postoperatively for comfort and protection without complications. 92 A major adverse effect of BCL wear is the risk of microbial keratitis and subepithelial infiltrate. 4 Recently a vitamin E loaded silicone contact lens that can provide continuous anesthetics release for about 1 to 7 days has been described.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%